Carrier Concentration in Bulk Perovskite CH3NH3PbI3 Thin Films - Mosiori, Cliff Orori; Charles, Mogunde (Engineering International, 2019)
Efforts are currently on going on the physics of photo electrics in methyl ammonium lead halide perovskites to unveil the secret of its success in photovoltaics. Since carrier concentration depends on impurity, temperature and other parameters of a semiconductor, herein, an attempt has been made address the relationship between these parameter and carrier concentrations. It was found out that the conventional band edge at 1.58 eV responsible for presenting a blue-shift depends on thickness, temperature and carrier concentration. Thus, in this work, the intrinsic carrier concentration was taken as the number of electrons and it was shown that the observed unusual optical band edge in CH3NH3PbI3 perovskite bulk thin films is about 1.58eV. It was concluded that the band edge is beneficial for photo electric effect by making use of its inhibited radiative recombination.